STUDI PENGEMBANGAN PANTAI WISATA MARUNDA JAKARTA - Faizal Ritonga, Arif
Abstract: Sediment is the most important factor for coastline change. In order to return Marunda beach into its first condition, Which was formerly visited by many people, it is needed a construction of groin placed vertically to the beach to catch the sand. The sediment moves along surf zone that is from broken wave to the beach, which is due to long shore current. The long shore current is due to the wave coming from the deep sea and forming an angle to the normal of coastline. Marunda beach is the object of this study, which has the length of coastline for more or less 2.3 km. The sediment consists of fine sand which composition above 80% with residual sludge. It has a sloping angle of 1 : 60 and surf zone of more or less 260 m. The dominant wind comes from northeast so that the dominant wave comes from northwest. In analyzing the sediment, it is used the energy fluctuation method. The result shows that the sediment discharge is 43068.58 m3/year. In order to return Marunda beach into its first condition, it is needed a simulation of analyzing method of coastline change that is the simulation of Pelnard Considere and Hsu method. From both analyzing method, it shows that the coastline will be full after 1.7 year only by using a 200 meter long groin. However, if two groins are used, the coastline will add for at least 20 m, Lkl will add for 45 m and Lk2 will add for 165 m. The beach area is 71500 m2 , and the distance of Lk2 groin from Lkl groin is 800 m.